Revealing offering culture suguh sesajen - Anxy Yudhatama Ghozuan (Universitas Airlangga, 2020)
In this modern era, we can get everything we want easily. Human most likely to use technology and think rationally. However, the people in Semen, Tanggalrejo Village, Mojoagung District, Jombang Regency is different because they still believe in the existence of supernatural things and routinely perform offerings activity called “suguh sesajen” to the Tomb of Bariden great grandfather and Mah great grandfather which are believed to be able to obtain good fortune and perform several rituals. This research uses qualitative methods by conducting in-depth interviews and observations. The results of this study indicate that the community still adheres to the tradition “suguh sesajen” offerings and believes in the myth of the occult power of the tomb.